Experimental and numerical investigation of ventilated cavitating flow structures with special emphasis on vortex shedding dynamics. (January 2018) - Wang, Zhiying; Huang, Biao; Zhang, Mindi; Wang, Guoyu; Zhao, Xing'an
Highlights: Ventilated cavitating flow structure is studied by a high-speed camera and a time-resolved particle image velocimetry (TR-PIV). The large eddy simulation (LES) model is proposed to simulate the unsteady ventilated cavity shedding process. A map is constructed to depict the various ventilated cavitation regimes. The mechanism of vortex shedding behaviors is illustrated. Abstract: The objective of this paper is to investigate ventilated cavitating flow structures with special emphasis on vortex shedding dynamics via combining experimental and numerical methods. In the experiments, the high-speed video and time-resolved particle image velocimetry (TR-PIV) technique are used to observe ventilated cavitating patterns, and to measure the flow velocity and vorticity fields. The numerical simulation is performed by CFX with large eddy simulation (LES) model to capture the unsteady cavity shedding process, and the corresponding velocity and vorticity dynamics. The results show that the flow patterns can be classified into two principally different categories: structures mainly with vortex shedding (namely Bénard–Kármán vortex street; Bénard–Kármán vortex street with vortex filaments and Aligned vortices) and relatively stable structures (namely Aligned vortices with Re-entrant jet; Re-entrant jet and Stable supercavity). For the structures mainly with vortex shedding, the Strouhal number St corresponding to vortex shedding frequency and ratio h/λ corresponding to vortex streets are significantly different in variable ventilated cavitating regimes: St and ratio h/λ increase with enhancement of gas entrainment coefficient Qv for the Bénard-Kármán vortex street, and then St declines gradually for Bénard-Kármán vortex street with vortex filaments and Aligned vortices, but ratio h/λ declines dramatically for the above both patterns. In addition, the influences of Qv on the velocity and vorticity distributions have also been investigated. The proper orthogonal decomposition (POD) analysis of PIV measurements is used to characterize the coherent large-scale flow unsteadiness of velocity fields. It demonstrates that the ventilated cavitation plays an important role in the first mode pairs to mainly affect the vortex shedding in the wake. Moreover, the vorticity transport equation is applied to illustrate the influence of ventilated cavitation on the vorticity distribution. It can be found that the associated vortex dilatation term and baroclinic torque term are important mechanisms for the complicated change of vortices.